PENGEMBANGAN MEDIA KOSABANG UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS SISWA KELAS IV SD - Nila Septri Setiawati; Maharani Oktavia; Kiki Aryaningrum (Universitas Negeri Medan, 2022)
Abstract: Interest in learning is an impulse that arises from within oneself to learn something from those who do not know. Therefore, the difficulty that arises is the low interest of students in learning, especially in social studies subjects. Based on this, the problem in this research is the learning media in the form of comics to increase students' interest in learning in social science subjects for class IV in elementary school. The purpose of this research is to develop comic media to increase students' interest in learning in social science subjects for grade IV in elementary school. This study uses the Research and Development method using the ADDIE model. The results of the research from the validation of experts get a percentage value of 89% with the criteria of